FUNDAMENTALISME PASAR DAN FUNDAMENTALISME AGAMA SEBAGAI ANTITESIS IDEOLOGI PANCASILA - Rizal A Hidayat (Jurnal Ilmiah Mimbar Demokrasi, 2013)
This article aims to explain how market fundamentalism and religious fundamentalism have a position opposite to the ideology of Pancasila. Today, two types of fundamentalism in the dominant ideology has become a challenge for the values of Pancasila. In the context of the nation of Indonesia, Pancasila ideology which has been the glue fundamental diversity of race, religion, race, culture, or group, has been degraded implementation intrinsic value, instrumental and praxis that seemed to be a utopian ideology against both types of fundamentalism in above. In practice the ideology of Pancasila is limited to less normative philosophy formulated well in the practice of national life.